Analysis of land cover change due to mining and its potential economic loss: A case study in the Bukit Soeharto Forest Park, East Kalimantan, Indonesia - SUNARTO SUNARTO; MARLON I. AIPASSA; RUJEHAN RUJEHAN; ALI SUHARDIMAN; ROCHADI KRISTININGRUM; YOSEP RUSLIM; WULAN IR SARI (Society for Indonesian Biodiversity, 2023)
Abstract. Sunarto, Aipassa MI, Rujehan, Suhardiman A, Kristiningrum R, Ruslim Y, Sari WI. 2023. Analysis of land cover change due to mining and its potential economic loss: A case study in the Bukit Soeharto Forest Park, East Kalimantan, Indonesia. Biodiversitas 24: 1206-1214. The Bukit Soeharto Forest Park in East Kalimantan, Indonesia, was once a conservation area but experienced annual land cover changes due to natural causes and human activities such as land clearing and mining. These changes can have economic, social, and environmental impacts. Therefore, this research aimed to analyze changes in land cover and potential economic losses from forest degradation due to mining in Bukit Soeharto research and Education Forest (BSREF) of Mulawarman University. It was conducted from April to October 2022, and the land cover analysis was performed using a series of maps from 2016 to 2022, which were classified based on an overlay technique with the aid of a GIS computer program. The economic valuation of environmental damage was calculated using guidelines from the Regulation of the Minister of Environment No. 7/2014, with a modified method based on the full cost principle. The results showed that the BSREF land, which covers 20,271 ha, experienced changes in the function of the area, with 702.86 ha being converted, resulting in a total economic valuation of environmental damage of approximately 29.6 trillion rupiah due to mining. Therefore, firm action from the local government is necessary to half further conversion and ensure the proper functioning of BSREF as a conservation area.